Hybrid watermilfoil lineages are more invasive and less sensitive to a commonly used herbicide than their exotic parent (Eurasian watermilfoil). (16th November 2012) - LaRue, Elizabeth A.; Zuellig, Matthew P.; Netherland, Michael D.; Heilman, Mark A.; Thum, Ryan A.
Abstract Hybridization may stimulate the evolution of invasiveness in human‐impacted habitats if unique hybrid genotypes have higher fitness than parental genotypes. Human efforts to control invasive taxa frequently involve the intentional alteration of habitats, but few studies have considered whether hybridization can result in decreased sensitivity to control measures. Here, we investigate whether interspecific hybrids between introduced Eurasian watermilfoil (Myriophyllum spicatum) and native northern watermilfoil (M. sibiricum) are more invasive than parental Eurasian watermilfoil, especially in regard to their relative responses to an herbicide commonly applied for their control (2, 4‐dichlorophenoxyacetic acid; 2, 4‐D). In two separate laboratory experiments, hybrids on average grew faster and were less sensitive to 2, 4‐D compared with parental Eurasian watermilfoil. These two invasive traits appear to be common in hybrid watermilfoils, as opposed to being restricted to a few unique lineages, because they were found in a diversity of hybrid genotypes from several independent hybridization events. In addition, we found that hybrids occurred more frequently than parental species in natural lakes previously treated with 2, 4‐D. Our results provide compelling empirical evidence that hybridization is associated with the evolution of increased invasiveness in watermilfoils, and have important implications for their management.